A microfluidic multiplex proteomic immunoassay device for translational research. Issue 1 (December 2015) - Cao, Jing; Seegmiller, Jesse; Hanson, Naomi; Zaun, Christopher; Li, Danni
Abstract Objective Microfluidic technology has the potential to miniaturize and automate complex laboratory procedures. The objective of this study was to assess a microfluidic immunoassay device, Simple Plex, which simultaneously measured IL-1β, TNF-α, IL-6, and IL-10 in serum samples. This assessment is important to understanding the potentials of this microfluidic device as a valuable tool in translational research efforts. Methods We studied the operational characteristics of Simple Plex, and compared to other immunoassay systems including bead-based (i.e., Bio-Plex® from Bio-Rad) and planar micro-spot based (i.e., Multi-Array from Meso Scale Discovery) multiplex assays. We determined imprecisions for each of the Simple Plex assays and evaluated the ability of Simple Plex to detect IL-1β, TNF-α, IL-6, and IL-10 in serum samples. Results Simple Plex assays required 25 µL serum, and 1.5 h to run 16 samples per cartridge per instrument. Assay imprecisions, evaluated by measurement of 6 replicates in duplicate from a serum pool using three different cartridges, were less than 10 % for all 4 cytokine protein biomarkers, comparable to the imprecisions of traditional ELISAs. The Simple Plex assays were able to detect 32, 95, 97, and 100 % [i.e., percentages of the results within the respective analytical measurement ranges (AMRs)] of IL-1β, TNF-α, IL-6, and IL-10, respectively, in 66 serum samples. Conclusions Simple Plex is a microfluidic multiplex immunoassay device that offers miniaturized, and automated analysis of protein biomarkers. Microfluidic devices such as Simple Plex represent a promising platform to be used in translational research to measure protein biomarkers in real clinical samples.